(untitled) (Journal of Bangladesh Academy of Sciences, 2016)
A total of nine species of fungi were found to be associated with seeds of nine varieties of chickpea. The isolated fungi were Alternaria alternata, Aspergillus flavus, A. niger, A. fumigatus, A. nidulans, Curvularia lunata, Penicillium sp., Rhizopus stolonifer and Trichoderma viride. Association of fungi with chickpea seeds was recorded three times, within a week after harvest, after two and five months of storage. The fungal association varied with duration of storage period. Species of Aspergillus, Penicillium and Rhizopus become predominating fungi with increase of the storage period. The fungal association with seeds of chickpea also affects germination, seedling mortality and seedling height. Germination of BARI chola 6 and 7 were completely inhibited due to prevalence of Rhizopus stolonifer in the seeds examined within seven days of harvest. The total fungal infection in chickpea seeds was highest in BARI chola 8 (168) and lowest in BARI chola 1 (65). Journal of Bangladesh Academy of Sciences, Vol. 40, No. 1, 37-44, 2016